Viabilidade técnica da produção de etanol a partir de farelo de arroz - Michel Junior, Raul José dos Santos (2016)
Currently there is great concern about the consumption of fossil fuels, as well as a possible depletion of traditional sources of production of raw materials mainly hydrocarbon derivatives. Parallel challenges to the preservation of the environment bring to discussions agenda every question involving biofuels and their means of obtaining. That said this issue still has major concerns about the use of raw materials that require less energy expenditure and prevent competition for land for food production, which end up entering the agenda of externalities related with this issue. In the case of the production of ethanol from starch sources, traditional processes still have high costs associated with the production of enzymes used and the great energy demand for starch gelatinisation at high temperatures. An alternative to the granular starch hydrolysis process is the use of enzymes capable of processing these starches at low temperatures which makes it unnecessary to gelatinization and reduces energy expenditure, also called simultaneous saccharification and fermentation (SSF), resulting in considerable economic advantage. Brazil is a traditional agricultural producer, and the rice production is quite significant and is as a by-product of rice bran that has low commercial value, being used for oil extraction, as an ingredient in animal feed and as fertilizer organic therefore be in perfect conditions to be used as raw starchy material to obtain ethanol. This work aims to investigate the use of this raw material and set the parameters for increased production scale-up with the use of commercial enzymes. The initial data to establish the working parameters were taken from the literature establishing this initial data for testing. In view of the large number of variables used to Plackett-Burman methodology to verify the effects of the main variables and select the ones that have most effect on the model.Thus for the job 1 in the shake flasks were selected following parameters: concentration of bran inoculum percentage, corn percentage of water macerated, soybean concentration, enzyme percentage yeast addition time and percentage of cellulase. This initial planning, among the most significant variables and, consequently, were selected for the planning application Outlining Central Composite Rotational (CCRD), are rice bran concentration, the percentage of inoculum and the percentage of cellulase. To work 2 were investigated variables agitation and temperature in ethanol production in bioreactor 3 liters. For analysis of the experiment of reducing sugar was used DNS method (Miller, 1959), and analysis of the ethanol present in the sample specimens were removed and subjected to Alcolyzer. For the tests performed in the first work the greatest amount of ethanol was obtained at 12 assay which was reached 172.70 grams of ethanol per kilogram of rice bran with 84% efficiency in the experiment. For experiments performed in the second study, with 3 liter reactor the best result is shown in Test 1 reaching 182.52 grams of ethanol per kilogram of rice bran with 89% efficiency. Thus, it was demonstrated that there is considerable potential for the production of ethanol using this raw material. Taking into account that the availability of this raw material is estimated at 1 million tonnes per year, the IRGA, we would have a much ethanol around 35 to 50 million liters per year.